Holistic Approach: Emotional Touch Intervention (Kissing and Hugging) and Macronutrient Nutrition in Stunting Prevention in Early Childhood) - Fitriahadi, Enny; Daryanti, Menik Sri; Nuzuliana, Rosmita; Mufdlilahi; Satriyandari, Yekti; Nguyen, Thuy Hong (Gema Lingkungan Kesehatan, 2025)
Stunting can lead to complications such as decreased intelligence and impaired growth, which may further deteriorate development into adulthood. This study aimed to examine the effectiveness of maternal kissing, hugging, and macronutrient intake in the prevention of stunting. A randomized clinical trial was conducted involving 170 mothers with toddlers aged 6 to 60 months who were at risk of stunting in 2024. Participants were randomly assigned to intervention and control groups. In both groups, parenting behaviors involving maternal hugging and kissing were measured using a structured questionnaire, while macronutrient intake, particularly protein-rich intake, was assessed using microtoise and length boards. The results showed a significant improvement in the intervention group compared to the control group (p < 0.001). The incidence of stunting was significantly lower in the intervention group than in the control group (p < 0.001). Additionally, the effectiveness of the Emotional Touch Intervention (Kissing and Hugging) and Macronutrient Nutrition (a local playful interaction technique) was statistically significant with a p-value of 0.000 (< 0.05). These findings indicate that maternal kissing, hugging, and adequate macronutrient intake are beneficial strategies in stunting prevention among toddlers. This study contributes to health innovations by promoting a combined approach of affectionate parenting and nutritional support to enhance toddler health and well-being.